FAKTOR - FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK - Aji, Andri Waskita; Kartikaningrum, Dena (LPPM STIE YKPN Yogyakarta, 2024)
Taxes are state income whose value is very large to be used for the interests of the government and the welfare of society. Tax evasion is a legal act within the scope of taxation by exploiting regulatory loopholes and not violating tax provisions. A common phenomenon is reducing the tax burden that must be paid through various legitimate tax avoidance strategies. Researchers aim to determine the influence of corporate governance, profitability and capital intensity on tax avoidance in manufacturing companies listed on the IDX in the 2019-2022 time period. This research is quantitative. This research uses four independent variables, namely Corporate Governance, including Institutional Ownership, Audit Committee, Profitability and Capital Intensity. The dependent variable is Tax Avoidance. Secondary data consists of figures taken from the financial reports of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (BEI). The results of this research have no effect on tax avoidance. The audit committee has no effect on tax avoidance. Profitability has a negative effect on tax avoidance. Capital intensity has a negative effect on tax avoidance. Institutional ownership, audit committee, ROA, and Capital Intensity partly have a negative effect on Tax Avoidance.